Competency-Based and Ethical Assessment Models in Contemporary Islamic Pedagogy - Rahman, Najib Aulia (Yayasan Sinergi Kawula Muda, 2025)
This narrative review explores recent innovations and systemic reforms in assessment practices within Islamic education, focusing on student-centered approaches, digital integration, competency-based evaluation, and the influence of cultural-religious values. The study employs a structured methodology involving database searches (Scopus, ERIC, Google Scholar), Boolean keyword combinations, and rigorous inclusion-exclusion criteria. The review synthesizes empirical findings from peer-reviewed literature, analyzing trends and best practices across global Islamic educational contexts. Key results indicate that authentic and formative assessments enhance student engagement and reflective learning. Digital tools, though unevenly adopted, improve efficiency and access. Competency-based reforms support a holistic appraisal of cognitive, affective, and spiritual dimensions of learning. Meanwhile, diverse interpretations of Islamic values lead to varied assessment practices across regions. Systemic enablers such as government policy, institutional frameworks, and continuous teacher training—especially through models like Lesson Study and self-assessment—are pivotal to successful implementation. Despite these advancements, challenges remain in digital infrastructure, educator readiness, and policy alignment. This review calls for comprehensive, culturally grounded, and scalable reforms, recommending greater investment in capacity-building and adaptive policy design. It underscores that learner-centered and ethically aligned assessments are essential to meet the pedagogical goals of Islamic education in the 21st century.